ANALISIS AKUNTABILITAS DAN TRANSPARANSI PEMERINTAH DESA DALAM PENGELOLAAN ALOKASI DANA DESA DI KECAMATAN LAU BALENG KABUPATEN KARO - Parhusip, Poltak T.; Karo, Emia Br (Jurnal Riset Akuntansi & Keuangan, 2023)
This study aims to determine the picture of accountability and transparency in the management of village fund allocation in 2018-2020 in Lau Baleng District, Karo Regency. This research was conducted in Lingga Muda Village and Lau Baleng Village located in Lau Baleng District, Karo Regency which is approximately 5 km between Lingga Muda Village and Lau Baleng Village. Data analysis was carried out on reliability and transparency based on Permendagri Number 113 of 2014. The population of this study is the realization budget starting from the emergence of Permendagri number 113 of 2014 until now. The sample inthis study was taken from the realization of the 2018-2020 budget. The data analysis technique used is a comparative descriptive technique, namely a comparison between the village under study and Permendagri number 113 of 2014. The results of the study can be seen that the application of accountability in the management of Village Fund Allocation (ADD) in Lingga and Lau Baleng villages, Labu Baleng District, Karo Regency is classified as good with the involvement of village communities in planning village fund allocation, as well as responsibility in managing village funds. This is in accordance with Permendagri 113 of 2014. Even so, there are still some shortcomings, especially in reporting accountability in terms of implementation realization reports. The implementation of transparency in the management of village fund allocation (ADD) of village governments in Lingga and Lau Baleng villages, Lau Baleng District, Karo Regency is still lacking transparency due to the lack of openness to the community in managing village fund allocation in village development, then there are still many limitations of the community in obtaining information regarding the management of village fund allocation.